Experimental Investigation of Compacted Sand-bentonite Mixtures. (2016) - Proia, Roberta; Croce, Paolo; Modoni, Giuseppe
Abstract: An experimental investigation was carried on sand-bentonite mixtures, prepared with various proportions of its components. The samples were compacted by Standard Proctor procedure, in order to simulate the in situ placement method employed for earth embankments and landfills base layers. By analysing the results of the compaction tests different structure types are identified depending on the bentonite content. For a small amount of bentonite, the mixture keeps the properties of granular soils, while for higher bentonite contents there is a gradual transition to the typical mechanical behaviour of plastic clays. The interaction between sand and bentonite is investigated by Scanning Electron Microscope. Compressibility and permeability are measured by one dimensional swelling and compression tests.